The Key Roles of Interferon Lambda in Human Molecular Defense against Respiratory Viral Infections - Lozhkov, Alexey A.; Klotchenko, Sergey A.; Ramsay, Edward S.; Moshkoff, Herman D.; Moshkoff, Dmitry A.; Vasin, Andrey V.; Salvato, Maria S. (Pathogens (Basel), 2020)
Interferons (IFN) are crucial for the innate immune response. Slightly more than two decades ago, a new type of IFN was discovered: the lambda IFN (type III IFN). Like other IFN, the type III IFN display antiviral activity against a wide variety of infections, they induce expression of antiviral, interferon-stimulated genes (MX1, OAS, IFITM1), and they have immuno-modulatory activities that shape adaptive immune responses. Unlike other IFN, the type III IFN signal through distinct receptors is limited to a few cell types, primarily mucosal epithelial cells. As a consequence of their greater and more durable production in nasal and respiratory tissues, they can determine the outcome of respiratory infections. This review is focused on the role of IFN-λ in the pathogenesis of respiratory viral infections, with influenza as a prime example. The influenza virus is a major public health problem, causing up to half a million lethal infections annually. Moreover, the virus has been the cause of four pandemics over the last century. Although IFN-λ are increasingly being tested in antiviral therapy, they can have a negative influence on epithelial tissue recovery and increase the risk of secondary bacterial infections. Therefore, IFN-λ expression deserves increased scrutiny as a key factor in the host immune response to infection.